Determinants of Skilled Birth Attendance in Gandaki Province, Nepal - Thapa, Shrijana (Kutumbha vani, 2025)
This study is to explore the factors influencing the use of skilled birth attendance (SBA) among women of reproductive age (15-49) in Gandaki Province, Nepal, based on the 2022 Nepal Demographic and Health Survey (NDHS) data. Even though there have been significant countrywide advances in maternal health, unequal access to SBA still persists along socio economic and geographic, especially in Nepal's hill and mountain provinces where the situation is worse. The study employs the secondary data of the NDHS and cross-sectional design with binary logistic regression employed to analyze the utilization of SBA based on some socio-economic and demographic factors like birth order, age, education, caste/ethnicity, residence, religion, and household wealth quintile. Women with primary education were approximately seven times, and those with secondary education 35 times, more likely to utilize SBA compared to women who had no school education. Economic status possessed a clearly defined positive gradient where households with greater wealth had very much greater opportunities of using SBA. In contrast to the Dalit women, the Janjati and Brahmin or Chhetri women were significantly less likely to have received any kind of skilled delivery assistance throughout this period, which points to the existence of caste-based disparities of very long duration. Even though age, parity, and place of residence were not always significant factors, rural and high-parity women still formed the majority of non-users and thus remained vulnerable to the situation. The results indicate the need for maternal health interventions that are equity-oriented and that are able to cater the present-day women in terms of education, economic accessibility. Among the policy interventions, transport voucher programs, maternity waiting homes, and upgraded community midwifery services can provide a great deal of help in facilitating equal and universal access to SBA.